Advanced detection methods for traceability of origin and authenticity of olive oils. Issue 14 (21st July 2015) - Ou, Gaozhi; Hu, Rui; Zhang, Liangxiao; Li, Peiwu; Luo, Xinjian; Zhang, Zhaowei
<x xml:space="preserve">Abstract</x> This review focuses on the advances in the sensing and identification of adulteration of olive oil, including optical sensing, chromatography, nuclear magnetic resonance, and DNA-based methods.